A Simulation Study of Upgrading Urban Gasoline Taxis to Electric Taxis. (December 2016) - Deyang, Kong; Dan, Ma; Minmin, Wang
Abstract: Upgrading gasoline taxis to electric taxisis an important measure to achieve energy-saving and emission-reduction targets. Based on Santana taxis in Shanghai, a set ofelectric taximodels with 15-100kWh batteries are built and simulated by Advisor which is secondarily developed. Comparative analysis between electric taxis and Santana taxis is made from the viewpoint of lifecycle cost and "Well to Wheel"emissions. Besides, optimal capacity of batterieson electric taxis is discussed. Results show that electric taxiswith 60kWh batteries could satisfy power requirements and achieve optimal economy and emissions.